Analisis Rentabilitas untuk Mengetahui Efektivitas Penggunaan Modal dalam Menghasilkan Laba pada PT. Bank Syariah Indonesia - Totok Adhi Prasetyo; Ainun Putri DG Mallimpo; Adna Fika Abidah Ardeliana; Sarniati Sarniati (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
This research reviews the development of Islamic banking in Indonesia, with a focus on the financial performance of PT Bank Syariah Indonesia. Despite facing the 1998 financial crisis and the 2008 global economic downturn, Islamic banks have proven their resilience and ability to withstand the impacts of these crises. In 2015, the government proposed merging three state-owned Islamic banks to improve efficiency and foster the growth of the sharia-based economy. The primary aim of this article is to assess the financial performance of Bank Syariah Indonesia by analyzing profitability, liquidity, and solvency ratios. The research utilizes a quantitative descriptive approach, analyzing data from the bank's 2021-2022 financial reports. The results indicate that the bank's financial performance is strong, with profitability, liquidity, and solvency ratios categorized as good to very good. This article contributes to a deeper understanding of the role of Islamic banks in supporting the national economy through financial performance evaluation.